DINAMIKA IMPLEMENTASI PENYELENGGARAAN PEMERINTAHAN DAERAH - Ahmad Namlis (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2018)
Structuring of local government has been through various regulations and dynamics in its implementation, since the era of independence until the reform era. The substitution and refinement of a law to its refinement brings implications for the arrangement of powers and affairs undertaken by local governments. Aksentuasinya grapple on what to do in the local government to provide services and realize the welfare of the people. Finally up to the Act No. 23 of 2014 is strengthening the balance of authority between the provincial and district / city government and community involvement in the development process. Previously become the government authorities kew Kabagan / the city then became the affairs and authority of the provincial government.